A Study on Brown Seaweed Therapy ( Sargassum sp.) toward MDA Levels and Histological Improvement on Rat Foot Suffering Rheumatoid Arthritis - Fauziah Fauziah; Aulanni'am Aulanni'am; Chanif Mahdi (Chemistry Department, The University of Brawijaya, 2013)
Rheumatoid arthritis (AR), an autoimun disease, is characterized by the inflammation in the joint area caused an excessive of free radicals. An excessive of free radicals in the body cause oxidative stress, that increasing levels of malondialdehyde (MDA) as an indicator of lipid peroxidation and the decreasing levels of anti-oxidants. The treated with extract of brown seaweed (Sargassum sp.) intended to find out the MDA levels in serum and the histological of the foot joints rheumatoid arthritis rats. Malondialdehyde levels are determined through a TBA test (Thio Barbituric acid), meanwhile the histological of the rat foot joints was determined by Hematoxylen-Eosin staining (HE). The results showed the brown seaweed extract therapy (Sargassum sp.) was significantly (p <0.01) reduce levels of malondialdehyde (MDA) in the serum of 21,24% and improving histological foot joints rheumatoid arthritis rats.